The Nature of Consciousness Characterized by Means of Hypnosis - Casiglia, Edoardo; Gadotti, Erik (Advances in Social Sciences Research Journal, 2026)
This paper is a report anchored in prior experiments and aims to describe consciousness using hypnosis as an application of a methodology drawn from experimental science. Three premises were posited. The first, epistemological in nature, assumes that all reality experienced and created by the individual belongs to an internal representational reality. The second, that hypnosis is capable of acting precisely on this representative reality with profound effects on all its dimensions. The third, that mental representations have a receptor basis. The consequence of these three hypotheses is the ability of hypnosis to act on the receptor system with a consequent effect on representations. While it is now known that there is a strong correlation between the central nervous system, the endocrine system, the immune system, and the subject's representational world, the precise nature of these correlations and, consequently, how hypnosis works, is still unknown. The same is true for receptor systems. While the individual systems are known, their mutual interrelationships are much less well understood.